Kualitas Layanan, Harga dan Religiusitas Terhadap Minat Beli Produk Pembiayaan Murabahah Studi Kasus PT. BPRS Madina Mandiri Sejahtera Yogyakarta - Afifah, Afina Ayu; Salam, Abdul (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2023)
The development of Islamic Banking, especially Islamic People's Financing Banks in Indonesia is currently quite significant, this can trigger competition that offers murabahah financing products. With the existence it is hoped that it can improve the economy of the middle and lower classes of society. The purpose of this study was to find out how the influence of service quality, price and religiosity on the intention to buy Murabahah financing products at PT. BPRS Madina Mandiri Sejahtera Yogyakarta. This study used a quantitative with a cross section approach. There’s 90 samples customers BPRS Madina 2022 using the Yamane formula and processed by E-views 12.0. This research uses data analysis techniques used classical assumption tests, multiple linear regression, partial tests (t), simultaneous tests (f), and coefficient of determination (R2). The results of this study based on the (t) and (f) tests show that service quality has a positive and significant, price has a negative and religiosity has significant. Then the R square value of 0,25 indicates that the independent variable is able to influence the dependent variable by 25%. While the remaining 75% is explained by other variables outside this study.